2001
DOI: 10.1034/j.1600-079x.2001.300106.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal alterations in circadian melatonin rhythms of the European wild boar and domestic gilt

Abstract: The aims of the present study were: 1) to determine if the European wild boar exhibits a circadian pattern of melatonin secretion under its natural light environment; 2) to compare this pattern with the pattern in domestic pigs reared under the light environment typical for domesticity; and 3) to determine if there are seasonal alterations in melatonin rhythms. Four to six young, pure-bred, European wild boars and four to six cross-bred (Yorkshire x Finnish Landrace) domestic gilts were sampled at 2-hr interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 25 publications
5
28
1
1
Order By: Relevance
“…It is well known that the conditions under which boars are maintained have a significant impact on the quality of their ejaculates (Corcuera et al, 2002). It is believed that during domestication pigs lost their diurnal rhythm of melatonin secretion or it just weakened (Tast et al, 2001). Mediterranean climate research on photoperiod in boars showed no significant differences in semen parameters analysed, although there was a change in concentration and motility (Rivera et al, 2005).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It is well known that the conditions under which boars are maintained have a significant impact on the quality of their ejaculates (Corcuera et al, 2002). It is believed that during domestication pigs lost their diurnal rhythm of melatonin secretion or it just weakened (Tast et al, 2001). Mediterranean climate research on photoperiod in boars showed no significant differences in semen parameters analysed, although there was a change in concentration and motility (Rivera et al, 2005).…”
Section: Discussionmentioning
confidence: 80%
“…The quantity and quality of ejaculates are affected by animal and environmental factors such as breed, age, feeding, health status and season (Cheon et al, 2002). The seasonality of breeding performance in sows and boars is often discussed in the literature (Peltoniemi et al, 2000;Strzeżek et al, 2000;Basset et al, 2001;Tast et al, 2001). Changes in the composition of semen during the year may vary between 25% and 30% (Colenbrander & Kemp, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Several examples of photoperiodic variation in the amplitude of the MEL peak have been observed, for example, in the pig (McConnell and Ellendorf, 1987;Taste et al, 2001), mule , Siberian hamster (Lerchl and Schlatt, 1992;Steinlechner et al, 1995;Miguez et al, 1996;Ribelayga et al, 2000), European hamster (Vivien-Roels et al, 1992, 1997, and horse (Guérin et al, 1995). Annual variations in the amplitude of the nocturnal MEL peak are especially visible when animals are maintained in their natural environment.…”
Section: Multiple Regulation Of Pineal Melatonin Synthesis In Mammalsmentioning
confidence: 99%
“…Long light duration on lactating sows has an indirect positive influence on the return to oestrus after weaning via an increase in appetite. It has been shown that pigs adjust their circadian melatonin secretion according to changes in photoperiod (Tast et al, 2001a). Bassett et al (2001) found that melatonin implants which were inserted at the spring equinox were able to prevent seasonal anoestrus, thus providing further support for the contention that the duration of the daily photoperiod is the primary determinant of the reproductive seasonality.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of melatonin secretion transduces information of lighting conditions to the endocrinological control system of gonadotrophins in the hypothalamus (Malpaux et al, 1996;. A circadian secretion pattern of melatonin in the domestic pig is similar to that of the European wild boar (Sus scrofa), which is a short day breeder (Mauget, 1982;Tast et al, 2001a). There is preliminary evidence that reduced fertility traits due to changes in day length can be corrected by a simple and effective light programme (Foxcroft, 1997).…”
Section: Introductionmentioning
confidence: 99%